Fungal Rhinosinusitis: A Radiological Review with Intraoperative Correlation. Issue 2 (May 2017) - Ni Mhurchu, Elaine; Ospina, Javier; Janjua, Arif S.; Shewchuk, Jason R.; Vertinsky, Alexandra T.
The interaction between fungi and the sinonasal tract results in a range of clinical presentations with a broad spectrum of clinical severity. The most commonly accepted classification system divides fungal rhinosinusitis into invasive and noninvasive subtypes based on histopathological evidence of tissue invasion by fungi. Invasive fungal rhinosinusitis is subdivided into acute invasive and chronic invasive categories. The chronic invasive category includes a subcategory of chronic granulomatous disease. Noninvasive fungal disease includes localized fungal colonization, fungal ball, and allergic fungal rhinosinusitis. Noninvasive disease is simply fungal material (or the products of the inflammatory reaction of the sinus mucosa) that fills the sinuses but does not invade tissue. Bone loss is related to expansion of the sinus(es). Invasive disease causes tissue destruction, such that it expands past the bony confines of the sinuses. It can rapidly spread, causing acute necrosis. Alternatively, there may be slow tissue invasion characterized by symptoms confused with normal sinusitis, but destruction of normal nasal and paranasal structures.